The Effect of Special Exercises for Developing Motor Response Speed and Some Refereeing Skills of New Basketball Referees - Muhameed, Wisana; Mtasher, Firas (Journal of Physical Education, 2020)
Refereeing is considered an integral pillar of basketball that plays a role in decreasing refereeing errors thus the importance of the research lies in designing special exercises for developing motor response time and some refereeing skills of new basketball referees and qualifying them for administrating matches. The researchers used the experimental method on (8) students from physical education and sport sciences college participating in the refereeing course held by the National basketball federation. The results showed that the proposed exercises have a positive effect on developing motor response time as well as training in game like situation have a great effect on developing refereeing skills in the subjects understudy.